Erythrocyte glycolytic and redox metabolism affects muscle oxygenation and exercise performance: a randomized double-blind crossover study in men - Chatzinikolaou, P. N.; Margaritelis, N. V.; Paschalis, V.; Theodorou, A. A.; Moushi, E.; Vrabas, I. S.; Kyparos, A.; Fatouros, I. G.; D`Alessandro, A.; Nikolaidis, M. G. (Sports Medicine, 2025)
Background: Erythrocytes are traditionally considered passive oxygen carriers, yet their energetic and redox metabolism plays a critical role in regulating oxygen kinetics. Objective: This study integrates experimental and computational data to provide a comprehensive analysis of erythrocyte metabolism in response to exercise-induced oxidative stress. Methods: The study consisted of three phases: in vivo, ex vivo, and computational. A total of 20 male participants underwent a randomized crossover experiment with two conditions: oxidative stress (eccentric contractions) and control. Oxidative stress was induced via leg eccentric contractions, and its effects on erythrocyte glycolytic and redox metabolism, arm muscle oxygenation, and arm exercise performance were evaluated. The study protocol was preregistered on the Open Science Framework (https://osf.io/ub6zs). Results: Eccentric contractions altered oxidative stress markers in erythrocytes (+ 22% F2-isoprostanes, + 28% protein carbonyls, - 20% glutathione). Oxidative stress increased erythrocyte glycolytic flux by + 53%, while arm exercise further increased glycolytic flux in both control (+ 200%) and oxidative stress (+ 86%) conditions. Exogenous hydrogen peroxide administration reduced glycolytic flux by - 48%. Stoichiometric analysis revealed that during acute exercise, erythrocytes produced 14.9% less ATP, NADPH, and 2,3-bisphosphoglycerate than their theoretical maximum, at the critical bioenergetic point. Oxidative stress decreased arm deoxygenated hemoglobin by - 7.4% during arm exercise and VO2peak by - 4% during arm exercise. Conclusion: In a comprehensive exercise study investigating mechanistic relationships in erythrocyte biology, we show that erythrocyte metabolism (1) responds dynamically to exercise, (2) becomes dysregulated under oxidative stress, and (3) may partly influence muscle oxygenation and performance.